PENGARUH PENGGUNAAN FLIPBOOK BERBASIS PENDEKATAN PROBLEM BASED LEARNING TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PESERTA DIDIK KELAS VII SMP IT MADANI ISLAMIC SCHOOL PAYAKUMBUH - Zaini, Muhammad; Suherman, Suherman (Jurnal Edukasi dan Penelitian Matematika, 2024)
Acquiring proficiency in mathematical problem solving is a crucial objective for students in their study of mathematics. However, the actual mathematical problem-solving proficiency of seventh-grade students at SMP IT Madani Islamic School Payakumbuh is still comparatively deficient. This is evident from the preliminary examination outcomes of students who have demonstrated inadequate proficiency in effectively resolving mathematical issues, as indicated by their mathematical problem-solving aptitude. To address these challenges, one possible solution is to implement a problem-based learning (PBL) flipbook learning approach. The research methodology employed in this study was Quasi Experiment, specifically the Nonequivalent Posttest-Only Control Group Design. The findings indicated that the students in class VII of SMP IT Madani Islamic School Payakumbuh who utilized PBL-based flipbooks had superior mathematics problem-solving skills compared to their peers who relied on conventional teaching materials.Keywords– Mathematical Problem Solving Ability, Flipbook, Problem Based Learning, Conventional, Teaching Materials